1990
DOI: 10.1111/j.1365-2842.1990.tb01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Etched glass ionomer liners: surface properties and interfacial profile with composite resins

Abstract: The purpose of this study was to assess the surface alterations induced by acid etching on two glass ionomer lining cements (Ketac Bond, G-C lining cement) and to evaluate their interface with a composite resin (Herculite XR) following various surface treatments. The changes in the surface composition and topography of the etched liners were studied by electron microprobe and ESCA analyses. The interfacial treatments performed on the ionomer surfaces were: (i) application of a bonding resin; (ii) 20-s acid etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The present study was designed to look purely at the potential seal between the materials themselves in as near ideal circumstances as possible. Taggart & Pearson (1988& 1991 showed that excessive etching, for more than 10-15s, can be detrimental to the surface of the cement, a finding supported by Papagiannoulis, Eliades & Lekka, (1990). The period of 10s of etching used in the present study would appear, therefore, to be acceptable from this point of view and to minimize destruction of the cement surface.…”
Section: Discussionsupporting
confidence: 61%
“…The present study was designed to look purely at the potential seal between the materials themselves in as near ideal circumstances as possible. Taggart & Pearson (1988& 1991 showed that excessive etching, for more than 10-15s, can be detrimental to the surface of the cement, a finding supported by Papagiannoulis, Eliades & Lekka, (1990). The period of 10s of etching used in the present study would appear, therefore, to be acceptable from this point of view and to minimize destruction of the cement surface.…”
Section: Discussionsupporting
confidence: 61%
“…In both the previous experiments mentioned, the GIC was used as a restorative material [28, 35]. As a dentine substitute, traditional GIC has been clinically used as lining material in the open and closed sandwich techniques [36] with a main issue being the optimum treatment of its surface for a durable adhesion with the resin composite [37]. …”
Section: Discussionmentioning
confidence: 99%